Advanced studies in media : communication and production - Nicholas, Joe, 1951-; Price, John. (Walton-on-Thames : Nelson, 1998)
Advanced Studies in Media has been designed to offer a comprehensive and stimulating textbook for all students on advanced level media studies and communications studies courses.
Includes bibliographical references and index.
Keywords: Mass media; Mass media -- Problems, exercises, etc; Media Studies